UNIVERSITY NOTES. (The Accounting Review, 1928)
This article provides information about various Universities. In the University of Arkansa, enrollment in both elementary and advanced accounting classes has shown more than 50% increase this year. Several public accounting firms have indicated their willingness to employ students during the month of January. In the University of California at Los Angles, Mr. Arthur Lorig has left the department to become Secretary and Treasurer of the Cypress Petroleum Co. Mr. Nathan Silverstein has been appointed associate in economics and accounting. In the University of Chicago, Mr. J.H. Cover, director of the bureau of business research at the University of Pittsburgh, has been appointed professorial lecturer in economics for one year to conduct research in the consumption of meat and meat products. The University of Chicago Law school has added a special course in accounting to the regular law curriculum, it may be applied toward requirements for the L.L.B. degree. In the Louisiana state University, Mr. James B. Trant has been appointed as the dean and professor of banking, formerly head of the department of Banking and Finance at the University of Texas.